'Indicators of competitiveness in the Eastern Caribbean Currency Union' (Caribbean Centre for Money & Finance [St. Augustine]TT, 2002)
Seeks to identify additional indicators (beside the REER) that can be used to more fully assess developments in external competitiveness of the region. Calculates and discusses developments in these indicators for the case of St. Lucia for the period 1992 to 2002.
Keywords: MONETARY POLICY